Safety Indications of Navigation Audit for Tankers to Develop a Bridge Inspection Method - Altun, Murat Hasan Ali; Kum, Serdar (Scientific Research Publishing, Inc., 2019)
A significant amount of world trade has been carried out by maritime transportation. In 2016, world maritime trade volume increased by 2% and reached 10.3 billion tons, 55,057 global ton-miles. There has been a significant increase in quantity and tonnage of tankers, with the requirement for well qualified and experienced personnel in the maritime industry. Therefore, employment has become a serious problem. Major Oil Companies (MOCs), port states, classification societies, and flag states have increased the number of inspections on tankers due to safety concerns. Tanker inspections are becoming more difficult and inefficient due to intensive cargo operations. Inefficient, subjective or substandard inspections/evaluations are usually leading to incorrect decisions, and causing an unfair market. In addition, corrective actions cannot be carried out properly, and decision making authorities cannot give the best decisions about vessels and their operator companies due to lack of scientific methods. In this study, details are identified such as finding the root causes, identifying the risks, understanding the possible consequences, and determining the working areas during the ship crews’, operators’, auditors’ and charterers’ working and ship selection periods. Pairwise comparisons were carried out by means of surveys on ship masters (captains), chief officers, deck officers, and superintendents. Five criteria—Crew, Equipment, Company, Structure, and ISM (International Safety Management) were weighted using Analytical Hierarchy Process (AHP). Finally, Bridge Safety Support System (BSSS) was developed according to criteria weights. In this way, best choices can be offered to ship charterers about which ship is better for a company’s interests. And, carrying out bridge inspections and corrective actions will be more reliable and effective for maritime transportation. Statistical data and vessel improvements will be obtained in BSSS. As a result, fair market conditions will be available in maritime industry with the help of this study.